Potholes in the Implementation of Printed Module in Mathematics and Feedbacks of Learners in Lambayong National High School During Covid-19 Pandemic - Elmer JR.P Serra; Nikko Jay R. Senope; Charls M. Lariosa (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of the study was to determine the potholes encountered by the students and their feedbacks in implementing printed modules in National High School in the Philippines. Mixed qualitative and quantitative were used, utilizing an adoptive modified five-point Likert’s Scale survey questionnaire to 100 students. The finding reveals significant relationships between the academic grades of the students and the potholes in the printed module in mathematics in terms of distribution and retrieval/submission and the assessment of feedbacks indicates no or negligible relationship. 31% commented that they are having problems with math in the modular setup from low motivation, caused by math anxiety resulting in poor understanding on how to apply and perform mathematical operations. 34% suggested that the graphics be made clear because they encountered cloudy graphics and the number was too small for being read. The potholes in the printed module cannot affect the academic performance of the respondents. Results of this study may serve as a basis for individuals who are involved in teaching mathematics during a pandemic for improving the quality of the printed module for a better learning experience from home.